Long-Term Effects of Aircraft Noise Exposure on Vascular Oxidative Stress, Endothelial Function and Blood Pressure: No Evidence for Adaptation or Tolerance Development - Frenis, Katie; Kalinovic, Sanela; Ernst, Benjamin P.; Kvandova, Miroslava; Al Zuabi, Ahmad; Kuntic, Marin; Oelze, Matthias; Stamm, Paul; Bayo Jimenez, Maria Teresa; Kij, Agnieszka; Keppeler, Karin; Klein, Veronique; et al. (Frontiers in Molecular Biosciences, 2022)
Transportation noise is recognized as an important cardiovascular risk factor. Key mechanisms are noise-triggered vascular inflammation and oxidative stress with subsequent endothelial dysfunction. Here, we test for adaptation or tolerance mechanisms in mice in response to chronic noise exposure. C57BL/6J mice were exposed to aircraft noise for 0, 4, 7, 14 and 28d at a mean sound pressure level of 72 dB(A) and peak levels of 85 dB(A). Chronic aircraft noise exposure up to 28d caused persistent endothelial dysfunction and elevation of blood pressure. Likewise, reactive oxygen species (ROS) formation as determined by dihydroethidium (DHE) staining and HPLC-based measurement of superoxide formation in the aorta/heart/brain was time-dependently increased by noise. Oxidative burst in the whole blood showed a maximum at 4d or 7d of noise exposure. Increased superoxide formation in the brain was mirrored by a downregulation of neuronal nitric oxide synthase (Nos3) and transcription factor Foxo3 genes, whereas Vcam1 mRNA, a marker for inflammation was upregulated in all noise exposure groups. Induction of a pronounced hearing loss in the mice was excluded by auditory brainstem response audiometry. Endothelial dysfunction and inflammation were present during the entire 28d of aircraft noise exposure. ROS formation gradually increases with ongoing exposure without significant adaptation or tolerance in mice in response to chronic noise stress at moderate levels. These data further illustrate health side effects of long-term noise exposure and further strengthen a consequent implementation of the WHO noise guidelines in order to prevent the development of noise-related future cardiovascular disease.